Ecological Protection Reasoning in Exegesis of Qur’an Surah Al-A'raf [7]: 56 in the Medieval Period - Sofyan, Muhammad Ilham; Arifin , Jainul; Nadhiya, Syarifah (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2024)
As ecological crises intensify globally, environmental themes have become prominent in contemporary Qur'anic exegesis (tafsir). However, ecological interpretation had its own distinct dynamics during the medieval period, even though environmental degradation was not as severe as in recent decades. The interpretation of nature protection in Qur'an Surah Al-A'raf [7]: 56 reveals diverse understanding among medieval scholars, challenging the notion that pre-modern interpretations were purely fragmentary or ideological. This study addresses two research questions: a) How was Q.S. Al-A'raf [7]: 56 interpreted ecologically in the medieval period? b) What hierarchical environmental ethics emerge from these medieval interpretations? Using qualitative methodology through literature review, this research focuses on the phrase "la tufsidu fi al-ardi" ("do not cause corruption on the earth"). The study analyzes interpretations from the ninth to fourteenth centuries as primary sources, employing Richard Sylvan and David Bennet's environmental ethics framework. The findings reveal three distinct interpretative approaches to the prohibition of earthly corruption: anthropocentric, ecocentric, and theocentric. The prevalence of theocentric interpretations demonstrates that theological argumentation remained central even when addressing material ecological issues. Environmental degradation was understood not merely as physical exploitation but as spiritual corruption resulting from human disregard for divine ordinances. This research contributes to understanding the continuity between pre-modern and modern ecological interpretations, suggesting the value of interdisciplinary approaches linking Islamic exegesis with contemporary environmental policy.